2004
DOI: 10.1111/j.1467-9221.2004.00384.x
|View full text |Cite
|
Sign up to set email alerts
|

Threat as a Motivator of Political Activism: A Field Experiment

Abstract: The research reported here examined the effects of two potential motivators of political activism-policy change threat and policy change opportunity-in a field experiment. Different versions of a letter were sent by a political lobbying organization to potential contributors. One version highlighted threats of undesirable policy changes, another version highlighted opportunities for desirable policy changes, and the third version did neither. Policy change threat increased the number of financial contributions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
100
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(107 citation statements)
references
References 21 publications
5
100
2
Order By: Relevance
“…This insight would not be possible through the use of nationally representative probability samples, conventional student samples, or other online opt-in methods such as MTurk. The SMIS approach could be useful in this type of targeted research, as well as extended to recruit specific populations of interest to political scientists who study, for example, the dynamics of collective action or opinion among members mobilized around a specific political issue such as environmental protection, gay marriage, or legalized abortion (Klar and Kasser 2009;Mathy et al 2002;Miller and Krosnick 2004;Simon and Klandermans 2001;Thomas, McGarty, and Mavor 2009).…”
Section: The Smis Approachmentioning
confidence: 99%
“…This insight would not be possible through the use of nationally representative probability samples, conventional student samples, or other online opt-in methods such as MTurk. The SMIS approach could be useful in this type of targeted research, as well as extended to recruit specific populations of interest to political scientists who study, for example, the dynamics of collective action or opinion among members mobilized around a specific political issue such as environmental protection, gay marriage, or legalized abortion (Klar and Kasser 2009;Mathy et al 2002;Miller and Krosnick 2004;Simon and Klandermans 2001;Thomas, McGarty, and Mavor 2009).…”
Section: The Smis Approachmentioning
confidence: 99%
“…Second, we were expecting to confront political solidarity practices against civic solidarity practices through the analysis on community-regarding orientations. To our surprise the models showed that community-regarding concerns do not explain the variation between political and civic solidarity-based behaviours as for volunteerism and activisms (Kleres 2017;Omoto et al 2010;Miller and Krosnick 2004;Caputo 1997) but the variation of political solidarity engagements between the groups as partially suggested in Hypothesis 3b. Thus, we underscore the importance of the motivational orientations to unveil the support or lack of support to migrants and refugees' populations confronted to unemployed people and to people with disability.…”
Section: Differentiating Civic and Political Solidarity Practicesmentioning
confidence: 75%
“…We note, however, given how unresponsive donation behavior was to our treatments, that our lack of difference may stem more from a lack of power than from a lack of actual differences (as seen in, e.g., Miller and Krosnick, 2004) 18 . Both positive and negative letters, however, served to stimulate giving among Democrats, as neither candidate received donations from the control group during or after the period of the study.…”
Section: Campaign Contributionsmentioning
confidence: 97%
“…A negative message may simply "stand out" against a general backdrop of positive information and life experience (Lau, 1985). Or, they may draw attention to possible costs or losses to avoid, which may receive more attention if voters are loss averse (Kahneman and Tversky, 1979;Jain et al, 2007;Miller and Krosnick, 2004) 7 . Our results do not support the hypothesis that negative messages are more memorable than positive ones.…”
Section: Introductionmentioning
confidence: 99%